Here, there and everywhere: nationalism after Brexit. Issue 8 (20th June 2020) - Favell, Adrian
ABSTRACT: Sivamohan Valluvan's The Clamour of Nationalism offers a convincing diagnosis of how a protean ideology of nationalism has successfully wound its way through the mainstream politics of the right and the left in the UK, laying the ideational foundations for Leave's victory, and the rise of Boris Johnson to power. Bringing to bear the powerful legacy of critical race studies after Hall and Gilroy, it sucessfully shows how and why English nationalism in the UK has marginalized its previously pioneering context of multiculturalism and cosmopolitanism. Aside from some hopeful examples of conviviality and multiculture in the Corbyn era, the book does not offer much to guide more positive thinking forward in the post-Brexit era.